KEMAMPUAN SPESIALISASI INDUSTRI AUDITOR MEMODERASI PENGARUH AUDIT TENURE DAN KUALITAS AUDIT SERTA PENGARUH RASIO KEUANGAN TERHADAP AUDIT REPORT LAG - Monica Kosasih; Rizka Indri Arfianti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2020)
Financial statements must be presented soon so it will not reduce its usefulness principles. This study aims to prove the effect of audit tenure and audit quality with auditor industry specialization as a moderating variable and also the effect of financial ratios to audit report lag. Research objects used mining sector companies listed on The Indonesia Stock Exchange for the period of 2016—2018 with an amount of 35 companies and a total of 105 observational data. The data analysis technique used descriptive statistic test, pooled data regression test, classic assumption test, multiple regression linear test, and hypothesis test using SPSS 20. The classic assumption test results show that the residual data is normally distributed, there is no symptom of heteroscedasticity, the regression model is free from multicollinearity, and there is no positive or negative autocorrelation. Based on this research, it can be concluded that there is sufficient evidence that solvability ratio has a positive effect on audit report lag, audit quality, and profitability ratio have negative effects on audit report lag. However, there is no sufficient evidence that audit tenure has a negative effect on audit report lag and auditor industry specialization doesn’t have the capability to moderate the effect of audit tenure and audit quality to audit report lag. Keywords: audit report lag, audit tenure, audit quality, financial ratios, auditor industry specialization